Organizational change in Algerian institutions - Boubertekh, Abdelkrim (Journal of Human Sciences, 2023)
Through this study, we aim to focus on the most important organizational changes that Algerian institutions have undergone and are going through. For this reason, we have studied a number of Algerian public and private institutions.Through this study, it was concluded that the internal and external environment of these institutions is characterized by instability, and therefore the Algerian institutions are pursuing a set of organizational changes with the developments taking place so that they can continue and achieve their goals.